From realism to neo-Kantianism. The case of Aleksander Świętochowski - the leader of Polish positivism - Sobieraj, Tomasz (My University, 2010)
The article is devoted to an interpretation of Aleksander Świętochowski'a essay entitled "Dumania pesymisty" ("The Pessimist's Thought). That work was published in 1876 and raised the question of the main rules of positivist philosophy. "The Pessimist's Thought" demonstrates interesting changes of Polish positivism which, in some apects, was transformed into an idealistic model of neo-Kantianism.
Keywords: Positivism; Neo-kantianism; Philosophy of nature